Characteristics of the school adaptation of college freshmen during the COVID-19 epidemic - Niu, Hua; Ren, Shuo; Li, Shuna (Frontiers in Psychology, 2022)
Few studies have actually explored the impact of the COVID-19 pandemic on mental health in college students, although many studies have suggested that the COVID-19 pandemic poses a great threat to people’s mental health in many cohorts. Furthermore, college students may be a particularly vulnerable cohort that needs more attention and access to psychological services due to the psychological changes involved in the transition to college and the characteristics of college students’ study habits and lifestyle. Therefore, investigating the basic characteristics of the impact of the COVID-19 pandemic on college freshmen is of great practical import and has theoretical implications for the identification of and provisioning of services to vulnerable cohorts. A total of 5,818 college freshmen completed the College Student Adaptability Inventory. The results suggest that the mean detection rate of the seven dimensions of undergraduate maladjustment to university is 27.13%. Specifically, livelihood self-management adaptability has the highest detection rate (48.93%), while environmental general evaluation has the lowest detection rate (9.81%). Moreover, the school adaptation of college freshmen is impacted by gender, number of siblings and family socioeconomic status (SES). Specifically, students who are female, an only child, and have a lower SES have lower levels of school adaptation. However, the school adaptation of college freshmen is not influenced by minority status or left-behind status. The findings of the present study suggest that the maladaptation of college freshmen has been a common phenomenon in China during the COVID-19 epidemic. Prevention programs may be most helpful if they pay more attention to effective intervention efforts for students who are female, an only child, and have a lower SES.